EMPOWERMENT OF UMKM THROUGH THE WEB OF SUKOJATI VILLAGE, BLIMBINGSARI DISTRICT: PEMBERDAYAAN UMKM MELALUI WEB DESA SUKOJATI KECAMATAN BLIMBINGSARI - Alfiyah, Nurul; Lukman Hakim; Karina Meidayanti; Paundra Afif Zamroni (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Service activities began by coordinating with Sukojati village officials and collecting data, as well as coordinating with PKK administrators regarding MSME data for creating the MSME website. Followed by providing basic concepts to village officials regarding the main functions of the application. Integration between product data on the village website This service also helps MSMEs in Sukojati Village sell products online through the Sukojati Village MSME website which will be linked to the Sukojati Village website. With product upload features and ordering integration via whatsapp, this website makes it easier for small businesses to promote and manage their sales.